The Effect of Public Trust on Individual Taxpayer Compliance with Minangkabau Culture as a Contextual Factor - Adriansyah; Zuriadah Ismail; Anis Suriati Ahmad (Institut Bisnis dan Informatika Kesatuan, 2025)
Tax compliance remains a challenge in Indonesia despite the growing number of registered taxpayers, particularly in West Sumatra, where socio-cultural values shape economic behavior. This study examines the effect of public trust on individual taxpayer compliance by incorporating the Minangkabau culture as a contextual factor. Using a quantitative explanatory design, data were collected from 393 individual taxpayers through a structured questionnaire and analyzed with Partial Least Squares–Structural Equation Modelling (PLS-SEM). The analysis assessed measurement validity and reliability, as well as structural relationships using R², F², and bootstrapping. Results indicate that public trust positively and significantly affects tax compliance (β = 0.309; p < 0.001), while Minangkabau culture also has a positive direct effect (β = 0.178; p = 0.005). However, its moderating role in the trust–compliance relationship is insignificant (p > 0.10). These findings emphasize that both institutional trust and cultural norms independently influence tax compliance. The study contributes to tax compliance literature by integrating institutional and cultural perspectives and suggests that tax authorities enhance transparency and incorporate local cultural values in community-based tax education.